Nonlinear Dynamic Responses of a Rotor-Bearing System with Eccentric Squeeze Film Dampers - Jiaqi Han; Wei Chen; Lulu Liu; Guihuo Luo; Fei Wang (International Journal of Aerospace Engineering)
A squeeze film damper (SFD) is a commonly used component in aeroengine support structures. However, eccentric SFDs are often employed in practical applications. Existing research in this field has mainly focused on simple rotor models and frequency-domain solution techniques. In this study, a rotor system tester with and without an eccentric SFD was built, and a simulation model based on the finite element method and fixed interface modal synthesis method was proposed. Then, the nonlinear dynamic response of the rotor system during run-up and run-down was studied based on the tester and simulation model. The results show that an eccentric SFD affords zero frequency and a series of double frequencies in the rotor system response. An eccentric SFD may cause the increase of the critical speed, amplitude jump, and displacement amplitude oscillation of the rotor system during run-up/run-down. Additionally, it may cause the acceleration response at the mounting bracket to significantly increase when the rotor system is suddenly accelerated.